Behavior and mood disorders in focal brain lesions (Cambridge University Press, 2000)
Behavior and Mood Disorders in Focal Brain Lesions takes a unique approach to presenting the emotional and behavioral consequences of focal lesions affecting the brain to summarize the current state of research and provide a basis for improved patient care. This is the first clinical reference work to specifically address the relationship of focal brain dysfunction to behavioral and emotional disorders, providing the most comprehensive account available of these manifestations of brain lesions including stroke, trauma, epilepsy, multiple sclerosis, and even neurosurgery.